Evaluation of quality circle programme implementation barriers in Indian SMEs with ISM methodology. (25th October 2022) - Attri, Rajesh; Chacko, Anwin Mathew; Kumar, Surinder
Quality circle (QC) has emerged as a valuable tool for the manufacturing as well as service organisations to solve their quality related issues. The key challenge of manufacturing organisations is to successfully utilise this quality tool for resolving the problems. In view of this, the current work targets to identify and evaluate the barriers of QC in Indian SMEs. In the present research work, 15 QC implementation barriers have been identified and afterwards, evaluated by using interpretive structural modelling (ISM) approach. The result of the present work can be effectively utilised by the top management to develop suitable strategy for effective utilisation of QC methodology.